Marketing strategy analysis to optimize lemigas assets as blu (public service agent) case study: lobp lemigas - Julois Pakpahan, Henry; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2018)
Abstract – This research was conducted based on the low acceptance of technological services from Lube Oil Blending Plant (LOBP) LEMIGAS as a government assets under Research and Development Center for Oil and Gas Technology “LEMIGAS”. In the year of 2017 LOBP LEMIGAS only worked 187,000 liters per year, while the maximum capacity that can be done by LOBP LEMIGAS is 10,000 tons/year. This means that the acceptance of LOBP LEMIGAS technology services in 2017 only reached 2.3% of the maximum production capacity. In addition, LEMIGAS as a Public Service Agency (BLU) is required to increase its revenue because the State Budget (APBN) for Research and Development will decrease every year. The issued of finance minister's regulation number 136 / PMK.05/2016 concerning the management of Public Service Agency (BLU) assets has opened up more opportunities to optimize LOBP LEMIGAS. The purpose of this study is to analyze the internal and external conditions of LOBP LEMIGAS. Furthermore, analyze the things that are a barrier to the development of LOBP LEMIGAS, and formulate the right marketing strategy. This study uses qualitative methods, where primary data is obtained from interviews with parties related to LOBP. While secondary data is obtained through a literature study. The results of the analysis of this research indicate that the current LOBP LEMIGAS expansion has proceeded well, but it is necessary to improve the marketing strategy so that the utilization of LOBP LEMIGAS assets can be optimized.Keywords: LOBP, BLU, Assets, Opportunities, Marketing strategy